Genome and Transcriptome Sequencing of Populus × sibirica Identified Sex-Associated Allele-Specific Expression of the CLC Gene - Pushkova, Elena N.; Krasnov, George S.; Lakunina, Valentina A.; Novakovskiy, Roman O.; Povkhova, Liubov V.; Dvorianinova, Ekaterina M.; Beniaminov, Artemy D.; Fedorova, Maria S.; Snezhkina, Anastasiya V.; Kudryavtseva, Anna V.; Dmitriev, Alexey A.; Melnikova, Nataliya V. (Frontiers in Genetics, 2021)
Transcriptome sequencing of leaves, catkin axes, and flowers from male and female trees of Populus × sibirica and genome sequencing of the same plants were performed for the first time. The availability of both genome and transcriptome sequencing data enabled the identification of allele-specific expression. Such an analysis was performed for genes from the sex-determining region (SDR). P. × sibirica is an intersectional hybrid between species from sections Aigeiros (Populus nigra) and Tacamahaca (Populus laurifolia, Populus suaveolens, or Populus × moskoviensis); therefore, a significant number of heterozygous polymorphisms were identified in the SDR that allowed us to distinguish between alleles. In the SDR, both allelic variants of the TCP (T-complex protein 1 subunit gamma), CLC (Chloride channel protein CLC-c), and MET1 (DNA-methyltransferase 1) genes were expressed in females, while in males, two allelic variants were expressed for TCP and MET1 but only one allelic variant prevailed for CLC. Targeted sequencing of TCP, CLC, and MET1 regions on a representative set of trees confirmed the sex-associated allele-specific expression of the CLC gene in generative and vegetative tissues of P. × sibirica. Our study brings new knowledge on sex-associated differences in Populus species.